Preoperative predictors of unplanned conversion in laparoscopic liver resection: a multicenter cohort analysis - Jiang, Yin; Yadav, Dipesh Kumar; Wang, Gaoqing; Jiang, Zhekang; Zhang, Shiwei; Cheng, Gong; Zhou, Xinhua; Wang, Haibiao; Li, Hong; Hu, Yiren; Hua, Yongfei (Frontiers in Oncology, 2025)
ObjectiveTo identify preoperative predictors of conversion from laparoscopic to open hepatectomy for optimized patient selection.MethodsThis retrospective cohort study analyzed 755 patients undergoing laparoscopic liver tumor resection at two tertiary centers (December 2019–June 2025). Patients were stratified by surgical approach: laparoscopic completion (n=709) versus unplanned conversion (n=46). Univariate analysis was performed using the chi-square (χ²) test for categorical variables and the independent samples t-test for continuous variables. Variables with a p-value < 0.05 were included in multivariate logistic regression analysis to identify independent risk factors for conversion. A p-value of <0.05 was considered statistically significant.ResultsThe conversion rate was 6.09% (46/755), predominantly due to uncontrolled bleeding (43.5%) and severe adhesions (34.8%). Multivariate analysis identified five independent predictors: history of abdominal surgery (OR = 2.12, 95%CI: 1.05–4.26); liver cirrhosis (OR = 5.34, 95%CI: 1.80–15.84); postero-superior tumor location (OR = 11.36, 95%CI: 5.49–23.52); extended resection (≥3 segments, OR = 2.80, 95%CI: 1.22–6.43); and extrahepatic organ resection (OR = 4.71, 95%CI: 1.13–19.56). Notably, while larger tumor showed univariate significance (p=0.041), it was not an independent multivariate predictor.ConclusionCritical preoperative risk factors for conversion include history of abdominal surgery, liver cirrhosis, tumors located in the postero-superior segment, extensive liver resection, and liver resection combined with extrahepatic organ resection. Careful selection of appropriate candidates for laparoscopic liver resection can help reduce the risk of conversion to laparotomy and the occurrence of further complications.